The Correlation of Individual Characteristics with Work Motivation Employeesat PT. Karunia Samudera Hindia (Kasahi) Sibolga City, North Sumatra - Esra Roida Sirait; Firman Nugroho; Ridar Hendri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT There are many factors that can cause employees’s motivation in doing their work. Some employees to work for the necessities of life, filling time, looking for work experience, etc. However, every individual working within the company will encounter of people's characters in the field. For that exact compression is required. This study aims to determine the correlation between individuals with motivation to work in PT. Karunia Samudera Hindia (Kasahi) using Rank Spearman analysis processed in SPSS 20. Keywords: Individual Characteristics, Work Motivation, Correlation